Muhammad the last prophet - Ismail, Imam Vehbi (Amana Publications, 2001)
There is a need by every Muslim to see the teachings of Islam put into practice. Since the life of Prophet Muhammad, in all its aspects, was the personification of the Quranic teachings, one has to read his biography to see Islam in action. Drawing on primary sources, Imam Vehbi Ismail presents a highly readable biography ' of the Prophet of Islam to the young American Muslims and adults. Who look for an authentic easy to read biography of the Last Prophet. The book is highly recommended for Middle and High School students and for inclusion in summer reading lists by schools and public libraries.